2018
DOI: 10.1111/geoj.12287
|View full text |Cite
|
Sign up to set email alerts
|

Subsistence migration: Smallholder food security and the maintenance of agriculture through mobility in Nicaragua

Abstract: Research on Central American migration has revealed the importance of journeys to the global North for rural sending communities. The outcomes of south–south journeys to nearby countries are less explored, although they are commonplace. We examine Nicaraguan rural residents’ migration to other Central American countries, especially El Salvador, to understand this migration's impacts on agricultural systems and food security. Based on mixed‐methods fieldwork in north‐western Nicaragua, we find that rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
1
7
0
1
Order By: Relevance
“…Thus, what our findings demonstrate for the Nicaraguan and Guatemalan sites is that slow displacement, manifest as this insufficient land for farming livelihoods, results in seasonal hunger. Our research suggests, as we also have demonstrated for the Somtillo case with findings published elsewhere [3], that migrant households in both sites employ earnings from migration to persevere in semi-subsistence agricultural production. While migration mitigates hunger for some migrant households, food insecurity persists for many families, even for many of those engaging in migration or receiving remittances.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Thus, what our findings demonstrate for the Nicaraguan and Guatemalan sites is that slow displacement, manifest as this insufficient land for farming livelihoods, results in seasonal hunger. Our research suggests, as we also have demonstrated for the Somtillo case with findings published elsewhere [3], that migrant households in both sites employ earnings from migration to persevere in semi-subsistence agricultural production. While migration mitigates hunger for some migrant households, food insecurity persists for many families, even for many of those engaging in migration or receiving remittances.…”
Section: Discussionsupporting
confidence: 88%
“…By the time the cooperatives were broken up, according to one farmer, "The most anyone had was 2 0.7 hectares. 3 Guatemalan Quetzal, with an exchange rate of 1 GTQ = 0.13 USD. about 20 manzanas, the rest of us had 10 or 8.…”
Section: Nicaragua: Working To Stay On the Land Through Subsistence Mmentioning
confidence: 99%
See 2 more Smart Citations
“…From a livelihoods perspective, migration is “one of a set of strategies that households and communities use to diversify and support well‐being” (De Haan, , p. 4), manage risks and buffer incomes (Black et al, ; Carte et al, ; Deshingkar, ; Tacoli, ), and realise personal aspirations (de Haas, ; Punch & Sugden, ). This recognises the multiple contextual drivers of migration that traverse micro‐ (individual and household), meso‐ (socio‐economic features of source and destination areas), and macro‐ (national and international policy landscape) scales (Adger et al, ).…”
Section: Migration As Adaptation: Examining the Evidencementioning
confidence: 99%